KNOWLEDGE OF HEALTH CARE PROVIDERS IN THE KINDU HEALTH ZONE ABOUT THE THREAT OF COVID-19 DISEASE - Bonny , ASSANI WAKENGE; ONYANGO , ROSEBELLA; OTIENO , CAREENA; Grace, KAMANA LELA; Thomas, MIANI BIKENGE; Hattie, NKAMBA NKANKOLONGO; Isaac , NKAMBA WA NKAMBA; Charles, WASONGA MUPENDA; Alphonse, MASANDI MILONDO (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2022)
Covid-19 threatens human life, endangers livelihoods and the way of life and the way of life of every individual in every society. Speed, scale and equity must be our guiding principles. Guiding principles. Speed, because the explosive nature of the virus means that every day lost in implementing effective response capabilities and response capabilities and behaviors costs lives , breadth, because everyone in society has a role to play in building the in building the capacity needed to control this pandemic; and to control this pandemic; and equity, because everyone is at risk everyone is at risk until the virus is controlled everywhere in the the world: collective resources must be directed to where the risks are greatest. COVID-19 is a truly global global crisis: the only way to overcome it is to unite is to unite in global solidarity.The overall objective is to assess the level of knowledge of providers at the General Hospital of Reference in Kindu, on the Covid-19 disease. Through a descriptive cross-sectional study of 70 health care providers based on a questionnaire survey the results revealed that 6 out of 10 health care providers surveyed have limited knowledge, about 3 out of 10 respondents have affordable knowledge and only about 1 out of 10 respondents have good knowledge. Based on this result, we conclude that the preparatory work for the prevention and containment of Covid-19 disease in the Kindu health zone is perceived as inadequate by the health care providers.